Analisis Kualitatif Terhadap Persepsi Efektivitas Gamifikasi e-Marketplace di Indonesia: Studi Kasus Kota Batam - Jose Manuel Budiman; Tony Wibowo (Teknik Komputer Politeknik Negeri Sriwijaya, 2023)
Currently, gamification and appearance are one of the main things that users pay attention to when visiting an e-Marketplace website. This is because the appearance is one of the main things user sees when visiting the website. Meanwhile, gamification helps in beautifying e-Marketplace websites with various features such as mini-games, ranks, and points. With the development of the game industry in Indonesia, the demand for game products such as top-ups, game-related merchandise, and some services such as game boosting is increasing. Seeing the relationship between the appearance of a website by users and the increasing popularity of e-Marketplace games that are full of potential, researchers researched to see user perceptions of the appearance of e-Marketplace games that implement gamification. The results of the study show that the implementation of this gamification can work properly. Other result include user perceptions also showing an interest in the interaction and experience of using display gamification of an e-Marketplace game.